Sexual harassment in Malaysian educational institutions: causes and solutions - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Trakic, Adnan; Mallow, Muzaffar Syah; Surajudeen, Ahmad Tijani (OCERINT International Oganizaiton Center Of Academic Research, 2015)
The vitality of school in proffering solutions to the societal challenges cannot be underrated. However, school as a hub and pivot place in addressing multifarious challenges in our society is faced with some social ills such as bullying and sexual harassment. More profusely, an escalation of sexual harassment in schools’ and on campuses cannot be denied. More copiously, of greater challenges in our contemporary period is inadequate and ineffective measure to curb prevalence of sexual harassment. More so, there are few existing guidelines in combating sexual harassment such as the Penal Code, Employment Act and the Code of Conduct for Industrial Harmony. However, there is yet to be a proper academic focus providing a deep investigation and crystal clear explanation in drastically minimizing or eradicating the prevalence of sexual harassment in schools and higher institutions of learning by formulating a policy and procedure in eschewing sexual harassment in schools in particular and society in general in the country. Hence, this paper elaborately explicates the various issues relating to sexual harassment in the Malaysian schools and higher institutions of learning and further, the various approaches towards its prevention.